2023
DOI: 10.3389/fpsyt.2023.1179257
|View full text |Cite
|
Sign up to set email alerts
|

The personality puzzle: a comprehensive analysis of its impact on three buying behaviors

Sibele D. Aquino,
Samuel Lins

Abstract: This study aimed at examining the role of personality traits in impulsive buying, compulsive buying, and panic buying simultaneously during the COVID-19 pandemic. At the beginning of the third confinement announced by the Portuguese government, 485 Portuguese answered in this study, mean age of 41.9 years (min = 18, max = 84; SD = 12.9), and 29.9% were men. Analyzes were carried out to investigate the association of Big Five’s personality factors with impulsive buying, compulsive buying, and panic buying. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 152 publications
1
0
0
Order By: Relevance
“…As far as the field of CB is concerned, although empirical evidence is limited, previous studies have found that the FFM traits have a critical role in explaining certain people's predisposition to developing CB [7]. More specifically, the findings obtained from this model thoroughly confirm that whereas neuroticism is a major risk factor for CB [10,21,23,24,[35][36][37][38][39][40][41], conscientiousness is a protection factor for this problem [21][22][23]37,39]. As for extraversion, most studies report positive, albeit modest, correlations with CB [23,41].…”
Section: Introductionsupporting
confidence: 54%
“…As far as the field of CB is concerned, although empirical evidence is limited, previous studies have found that the FFM traits have a critical role in explaining certain people's predisposition to developing CB [7]. More specifically, the findings obtained from this model thoroughly confirm that whereas neuroticism is a major risk factor for CB [10,21,23,24,[35][36][37][38][39][40][41], conscientiousness is a protection factor for this problem [21][22][23]37,39]. As for extraversion, most studies report positive, albeit modest, correlations with CB [23,41].…”
Section: Introductionsupporting
confidence: 54%
“…Psychological influences coincide with human traits, such as emotional instability, anxiety, low self-esteem and depression, and are considered a key factor in the development of compulsive behavior. Many recent studies have focused on a more detailed consideration of the connection between different personality characteristics and compulsive buying (Tarka, Harnish, & Babaev, 2022;Tarka, Kukar-Kinney, & Harnish, 2022;Otero-López, 2022;Moon, Faheem, & Farooq, 2022;Rizzo, Sestino, Pino, Guido, Nataraajan, & Harnish, 2023;Ali, Tauni, & Ali, 2023;Mert & Tengilimoğlu, 2023;Aquino & Lins, 2023). The genesis of compulsive buying behavior is linked to external factors like pricing, product promotion, and credit cards (Workman & Paper, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%